A.I. don't care:: aportes de la filosofía feminista de la tecnología para la Bioética cibernética - Benamo, María Eva (2023)
This paper examines the relationship between digital transformation and bioethics, drawing on insights from feminist theories of technology (TFT). The overall aim is to enrich the philosophical debate on biopolitical challenges (Bratton, 2021) that demand a robust bioethics, such as ecological catastrophe or the medicalization of life (Mainetti, 1990). The specific objectives are twofold: firstly, to explore the need to reinvigorate bioethics conceptually by reconnecting it with its neglected cybernetic origins (Potter, 1971), using concepts such as «antinaturalism» (Hester, 2019) and «antigenealogy» (Preciado, 2020). Secondly, to investigate the emergence of a «bioethification» (Calvo, 2019) that reflects the ethics of the mediations between humans, algorithms, and nature, using the notions of «care» (Nurock, 2020) and «dilemma» (Gilligan, 1982). In the first case, TFT allows us to avoid the moral absolutism of both technology and nature, without falling into their absolute relativization. In the second case, by analyzing AI devoted to care, TFT clarifies the impact of algorithmic systems on the development of moral competencies.